Effects of the Pillars of Competitiveness on the Competitive Positions of Poland and the Visegrad Group Countries in the Post‑Accession Period - Edward Molendowski; Paweł Folfas (Comparative Economic Research. Central and Eastern Europe, 2019)
The article presents the results of an analysis aimed at assessing the effects of fundamental factors (pillars) on the international positions and competitiveness of the economies of Poland and the other Visegrad Group (V4) countries. It attempts to verify the hypothesis that in shaping their international competitive position, the V4 economies should rely more on efficiency enhancers as well as innovation and sophistication factors. The competitive positions of the economies covered and the changes thereof were determined on the basis of the Global Competitiveness Report (GCR) editions published by the World Economic Forum. The period under examination includes the years 2004-2017, but owing to the lack of comparable data, it was narrowed to the years 2006-2017. The article ends with a summary of the most important conclusions from the analysis.
Keywords: E2; E6; F4; F5; 330; international economic competitiveness; pillars of the competitiveness of the Polish economy; Poland of the V4 countries